Minimalismo, un universo armonioso: análisis de la composición de los temas Fragment, Untitled y The Twins del álbum Memoryhouse de Max Richter, aplicado en un portafolio de tres composiciones - Maldonado Ribadeneira, Mauricio Hernán (2017)
The artistic inclination which is linked to the essential, and it is free from surplus components, is called minimal. Minimal is the propensity to minimize components into the most basic forms. This style is characterized by the use of pure colors, basic elements, and simple geometric shapes. Applying this concept to music, minimalism usually contains harmonies in a static tonality, using constant and repetitive pulses and rhythms. It contains melodic, harmonic and-or rhythmic patterns, but sometimes it can have slow motivic-rhythmic transformations. Another parameter that characterizes minimalist music is the complete antagonism towards the European integral serialism. This research gathered and exposed the most important elements of minimalist music. Therefore it was fundamental to determine this genre’s historical elements and how this style actually developed in music worldwide. The German composer Max Richter, in his album Memoryhouse, mixes concepts of minimalist, classic and electronic music. The songs of this album were recorded and performed by the BBC Philharmonic Orchestra. This piece of work contains a sort of electronic style, recited lines and performed songs in piano which provoke a minimalist style. This research contains a musical composition analysis of the songs Fragment, Untitled and The twins from the album Memoryhouse by Max Richter. In addition, this written work included a compilation of the leading exponents and composers of minimalist music worldwide. This research aims to disseminate minimalist music, promoting its history, its influences and its use. The study belongs to the emphasis of popular composition, and this is why the final product of this project, in addition to the written document, it is a portfolio of three compositions.